(untitled) (Pathibhara Journal of Multidisciplinary Research, 2026)
Motivation is crucial for second language learners. It impacts learners’ engagement, confidence, and willingness to learn. The aim of this study is to investigate the role of motivation in enhancing speaking skills in English language classrooms in Nepal. The present study attempts to explore the role of motivational strategies such as role-play, picture describing, and conversation in developing students’ speaking skills. I adopted an action research design, which was qualitative in nature. The steps of the research included 1) planning, 2) implementing, 3) observing, and 4) evaluating or reflecting. The required data were collected through tests. The sample size included twenty-eight students from grade 10 in Shree Siddhakali Secondary School in the Taplejung district of Nepal. The test scores of all four tests showed significant increments, which indicates that motivational strategies played a constructive role in developing students’ speaking ability. The findings underscore the significance of positive teacher-student interactions, technology integration, and addressing language anxiety in nurturing learners’ motivation. This research provides valuable insights for educators, policymakers, and language learning institutions to design effective strategies that foster a supportive and motivating learning environment, ultimately empowering ESL learners to achieve their language learning goals.